If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + 13 = 14x + -5 + -13x Combine like terms: -2 + 13 = 11 11 = 14x + -5 + -13x Reorder the terms: 11 = -5 + 14x + -13x Combine like terms: 14x + -13x = 1x 11 = -5 + 1x Solving 11 = -5 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 11 + -1x = -5 + 1x + -1x Combine like terms: 1x + -1x = 0 11 + -1x = -5 + 0 11 + -1x = -5 Add '-11' to each side of the equation. 11 + -11 + -1x = -5 + -11 Combine like terms: 11 + -11 = 0 0 + -1x = -5 + -11 -1x = -5 + -11 Combine like terms: -5 + -11 = -16 -1x = -16 Divide each side by '-1'. x = 16 Simplifying x = 16
| 3b-4/3 | | 3x=65.14 | | 3z+2z+z=3z+25+2 | | 6bc^2-28bc+16b=0 | | 3x+4ab=4x-5ab | | 5(2n+6)=-4(-5-2n)+3n | | 4(3x-7)=9(2x-5) | | (3/2)x-2=19 | | 12x^2-6/-4=0 | | x+35=35 | | -14-(-11)=x/11 | | 3x+10=2x+6 | | 5x-4=6x+9 | | 20+a=2a+10 | | 4y-7=2y-38 | | 2n^3-18n^2-14n=0 | | 6ds^2-28ds+16d=0 | | 3/5x-1/10x-5 | | Log(b)64=2 | | 14j+j+4j+j-18j=14 | | c^2-3*c-10= | | (5-3x)(2x-7)=0 | | 26=11.6+y | | 7p-2p=15 | | 25v=-125 | | 2w-w=11 | | 13c-3c=20 | | n-(-7)=26 | | 3(5x-5)=25.5 | | 8g-5g=18 | | 6x-2y=-36 | | 5x+23=14 |